Yu-Gi-Oh! R. Volume 2, A world ruled by fear! - Itō, Akira (Takahashi, Kazuki, 1961- Yu-gi-oh! R, 2010)
"Yugi's battle with Yako Tenma continues, but things are not as they seem! Yako's Evil God Cards are just as strong as Yugi's Egyptian God Cards, and at the height of the duel, they unleash their hidden supernatural power. Meanwhile, Yako reveals the true purpose of his sinister 'R.A. Project,' and why he needs Anzu's body. Can anyone stop his mad plan?" -- from publisher's web site.